Analisis Kualitas Pelayanan Terhadap Respons Deposan PD BPR Amanah di Kabupaten Bogor - Ferdian Arie Bowo; Iwan Ridwan; Asep Irwansyah (E-Journal Studia Manajemen, 2013)
Macro-economic risks may affect the action well apart from the depositor and by the characteristics of a particular bank. The effect of macroeconomic factors beyond the bank-specific characteristics may occur when the worsening macroeconomic conditions directly threatens the value of the asset to market participants (such as bank deposits). This study aims to describe the quality of service of the response Depositor PD BPR Amanah in Bogor. The method used by the authors is a quantitative method in the study population amounted to 150 people, while the sample of 60 people. The results showed that there are significant quality of service to the Depositor response.